Establishment of a Tumour–Stroma Airway Model (OncoCilAir) to Accelerate the Development of Human Therapies against Lung Cancer. Issue 5 (October 2016) - Mas, Christophe; Boda, Bernadett; Futy, Mireille Caul; Huang, Song; Wisniewski, Ludovic; Constant, Samuel
This paper highlights the work for which OncoTheis, a Swiss biotechnology company, engaged in the development of innovative bioengineered tissues and organoids for cancer research, was co-awarded the 2015 Lush Science Prize. Noting that the use of animal models failed to lead to the design of effective treatments for cancer, OncoTheis has opted to develop in vitro models based exclusively on human cells. The company currently focuses on lung cancer, which is the leading cause of cancer-related deaths worldwide, with more than one million deaths per year. To address this public health concern, we developed OncoCilAir ™, a new 3-D model that mimics in vitro the progression of the disease as it happens in patients. In this system, bronchial and lung tumour cells obtained from discarded surgical tissue are co-cultured in a Petri dish to reconstitute a fragment of the human lung. After appropriate differentiation, the culture closely reproduces malignant pulmonary nodules invading a small piece of functional airway tissue. As OncoCilAir includes both healthy and cancerous tissues, it can be used to test tumour-killing activity and the adverse effects of chemotherapies and other anti-cancer drugs. Moreover, a single culture can be maintained for up to three months, which permits studies of longer-term effects, including the assessment of drug resistance and tumour recurrence. OncoCilAir heralds a new generation of integrated in vitro models, which is expected to increase the quality of preclinical research while replacing animal testing.